An updated review of type 1 diabetes in Malaysia - Ahmad Mahfuz, Gazali (Kulliyyah of Medicine, IIUM, 2022)
The emerging phenomenon of early-onset type 2 diabetes mellitus (T2D) among Malaysians and misclassification of diabetes types may impact the estimates of prevalence and incidence of type 1 diabetes mellitus (T1D). From previous studies, the prevalence of T1D among the major ethnic groups in Malaysia was seen highest among Chinese, followed by Malays and Indians. More than half of the patients had diabetes ketoacidosis (DKA). This corresponded with the overall poor glycaemic control seen. However, the incidence of chronic complications, such as nephropathy, was lower. The prevalence of autoantibodies was reported highest for anti-islet cell antibody (ICA). As part of treatment, most Malaysian children had one or two daily insulin injections. Generally, older patients responded better to insulin therapy and yielded better glycaemic control than younger patients. While significant advances have been made in understanding T1D in the Malaysian population, more research is warranted to improve the clinical assessment and outcome of the disease. The present narrative review aims to summarise the overall status of T1D in Malaysia, which includes epidemiology, clinical presentation, diagnosis, complications, and management.